Sosialisasi Pencegahan Demam Berdarah Dengue pada Anak Sekolah Dasar Dusun Setro Kecamatan Bergas Kabupaten Semarang - Puji Purwaningsih; Zumrotul Chaerijah; Umu Muntamah; Gipta Galih Widodo (Lembaga Pengembangan Kinerja Dosen, 2024)
One way to raise awareness of love for the environment and prevent dengue hemorrhagic fever is through outreach to school children. Socialization is one way to increase knowledge about preventing dengue hemorrhagic fever. The outreach aims to control the increasing incidence of dengue hemorrhagic fever cases. The method used begins with observation and giving a questionnaire to be filled in regarding questions regarding dengue hemorrhagic fever. After the data is found, a nursing diagnosis is then formulated, followed by implementation activities in the form of edugames and community service. Pre post analysis of knowledge using the Wilcoxon test showed that the p value (0.000) showed that there was an increase in knowledge between before and after socialization.